Challenge Faced by Domestic Child Workers in Achieving School Education - Pyakurel, Rajaram (Sahayaatra सहयात्रा, 2024)
Domestic child workers work in an inside house with or without direct payment. Legally it is prohibited although socially, and culturally promoted in city areas. This article analyzes the challenges faced by domestic workers in the home, and how they are motivated to study in difficult situations. This article was based on the phenomenological study of domestic child workers from child rights perspectives. Data were collected through in-depth interviews with participants. On the basis of the data, two themes were generated and analyzed. A lot of the information that came in the form of data was based on the problem they ran into. It concludes that domestic child workers face physical, mental, and social problems in their r workplace (Home). Their children's rights were violated by their parents, and employers although were motivated to study to fulfil their future aims.